Bonding composite substrate and preparation method thereof, epitaxial structure and preparation method thereof, and device

By forming a quantum trap through the key interface of the 3C-SIC layer and the 4H-SIC layer, the problem of forming SIO2 insulation layers and poor pressure resistance in the existing technology in the existing technology, and realizing high-resistant pressure and low-conducting resistance resistance resistance Bonded composite substrate.

CN119372779APending Publication Date: 2025-01-28JINGFENG XINCHI (SHANGHAI) SEMICON TECH CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411684362.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, the bonding process causes the bonding interface to form a SiO2 insulating layer, increasing the resistivity, and at the same time, the bonding substrate has problems such as poor voltage resistance and easy etching during epitaxial growth etching.

Method used

Use a specific design bonding structure to form a quantum trap by forming a quantum trap on the key interface of the 3C-SIC layer and the 4H-SIC layer, so that the layer error is expanded to the key interface, thereby avoiding layer error to the single crystal layer or external delay layer, and enhancement For pressure resistance, and through low surface freedom, it can prevent thin monocular layers from engraving.

Benefits of technology

Improve the pressure resistance of the device, reduce the pitch resistance, prevent the thin single crystal carving through, and improve the overall performance of the key composite substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372779A_ABST
    Figure CN119372779A_ABST
Patent Text Reader

Abstract

The invention relates to a bonding composite substrate and a preparation method thereof, an epitaxial structure and a preparation method thereof, and a device, in particular to the field of power devices, and the bonding composite substrate comprises a polycrystalline SiC layer, a first 4H-SiC layer, a 3C-SiC layer and a second 4H-SiC layer which are bonded in sequence. According to the bonding composite substrate provided by the invention, by adopting the specifically designed bonding structure, the quantum well is formed on the bonding interface of the 3C-SiC layer and the 4H-SiC layer, and the fault is expanded to the bonding interface, so that the fault is prevented from being expanded to a single crystal layer and even an epitaxial layer, the pressure resistance is improved, and meanwhile, the obtained bonding composite substrate has relatively low surface free energy, so that the bonding performance is improved. The thin single crystal layer can be prevented from being etched through.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of power devices, and specifically to a bonded composite substrate and a preparation method, an epitaxial structure and a preparation method, and a device, and in particular to a bonded composite substrate and a preparation method, an epitaxial structure and a preparation method, and a device for MOSFET. Background Art

[0002] As a wide bandgap semiconductor material, silicon carbide devices made on silicon carbide substrates have the advantages of high temperature resistance, high voltage resistance, high frequency, high power, radiation resistance and high efficiency. They have important application value in radio frequency, new energy vehicles and other fields.

[0003] Currently in 750V MOSFETs, the drift region thickness is only 6-8μm, and the substrate will contribute up to 17% of the total device resistance. When conventional single-crystalline SiC substrates are grown by seed sublimation, there is a fundamental trade-off between crystal quality (low defect density) and doping density (low resistivity). Since the substrate is the basis for subsequent epitaxial growth, the quality of the substrate cannot be compromised, so its resistance is relatively high (typically 15-25mOhm-cm). The limited doping density of the substrate also adds to the small contact resistance (Rc) between the substrate and the drain. In contrast, when producing polycrystalline silicon carbide substrates, their defect density is not important, so their doping density can be pushed to the limit, thereby minimizing their resistance.

[0004] Therefore, by processing a high-quality SiC single crystal substrate and bonding the processed surface to a low-resistance polycrystalline SiC wafer as a supporting substrate, not only can the cost be reduced, but also the on-resistance can be reduced and device performance can be improved.

[0005] However, the existing bonding process is through hydrophilic bonding, SiC first forms Si-OH, and then squeezes out a H2O molecule, resulting in a SiO2 insulating layer on the bonding interface, which in turn increases the resistivity. At the same time, the existing bonding substrate still has the defects of poor voltage resistance and easy penetration during epitaxial growth etching. Summary of the invention

[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a bonded composite substrate and preparation method, an epitaxial structure and preparation method and device, so as to solve the problem that the existing bonding process leads to a SiO2 insulating layer at the bonding interface, thereby increasing the resistivity, and at the same time, the existing bonding substrate still has the defects of poor voltage resistance and easy etching through during epitaxial growth etching.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a bonded composite substrate, comprising: a polycrystalline SiC layer, a first 4H-SiC layer, a 3C-SiC layer, and a second 4H-SiC layer bonded in sequence.

[0009] The bonded composite substrate provided by the present invention adopts a specifically designed bonding structure and forms a quantum well at the bonding interface of the 3C-SiC layer and the 4H-SiC layer, so that the stacking fault is extended to the bonding interface, thereby preventing the stacking fault from extending to the single crystal layer or even the epitaxial layer, thereby improving the voltage resistance performance. At the same time, the obtained bonded composite substrate has a lower surface free energy and can prevent the thin single crystal layer from being etched through.

[0010] As a preferred technical solution of the present invention, the thickness of the polycrystalline SiC layer is 330-370 μm.

[0011] Preferably, the first 4H-SiC layer has a thickness of 0.3-0.7 μm.

[0012] Preferably, the thickness of the 3C-SiC layer is 0.3-0.7 μm.

[0013] Preferably, the second 4H-SiC layer has a thickness of 0.3-0.7 μm.

[0014] In a second aspect, the present invention provides a method for preparing a bonded composite substrate as described in the first aspect, the preparation method comprising:

[0015] Performing a first bonding between the 4H-SiC layer implanted with the first ions and the polycrystalline SiC layer, followed by a first stripping and a first polishing to obtain a first bonding body;

[0016] Performing a second bonding between the first bonding body and the 3C-SiC layer implanted with the second ions, and then performing a second peeling and a second polishing to obtain a second bonding body;

[0017] The second bonding body and the 4H-SiC layer that has been subjected to the third ion implantation are subjected to the third bonding, and then subjected to the third stripping and polishing to obtain a bonded composite substrate.

[0018] As a preferred technical solution of the present invention, the 4H-SiC layer used in the first ion implantation includes an N doping concentration of 5×10 18 -1×10 19 atom / cm 3 , 4H-SiC single crystal layer with a 4° deviation in the <11-20> direction.

[0019] Preferably, the implantation dose of the first ion implantation is ≥10×10 15 atom / cm 2 .

[0020] Preferably, the implantation energy of the first ion implantation is ≥80keV.

[0021] Preferably, the implantation angle of the first ion implantation is 5°-20°.

[0022] Preferably, the implantation depth of the first ion implantation is 0.5-1 μm.

[0023] Preferably, the first bonding method includes Ar ion activation.

[0024] Preferably, the bonding strength of the first bonding is > 1.5 J / m 2 .

[0025] Preferably, the temperature of the first stripping is 150-300°C.

[0026] Preferably, the first peeling time is 30-45 minutes.

[0027] Preferably, the surface roughness Ra of the first bonding body obtained after the first polishing is less than 0.2 nm.

[0028] As a preferred technical solution of the present invention, the 3C-SiC layer used in the second ion implantation includes a 3C-SiC single crystal layer with a 4° inclination in the <11-20> direction.

[0029] Preferably, the implantation dose of the second ion implantation is ≥10×10 15 atom / cm 2 .

[0030] Preferably, the implantation energy of the second ion implantation is ≥80keV.

[0031] Preferably, the implantation angle of the second ion implantation is 5°-20°.

[0032] Preferably, the implantation depth of the second ion implantation is 0.5-1 μm.

[0033] Preferably, the second bonding method includes Ar ion activation.

[0034] Preferably, the bonding strength of the second bonding is > 1.5 J / m 2 .

[0035] Preferably, the temperature of the second stripping is 150-300°C.

[0036] Preferably, the second peeling time is 30-45 minutes.

[0037] Preferably, the surface roughness Ra of the second bonding body obtained after the second polishing is less than 0.2 nm.

[0038] Preferably, the 4H-SiC layer used in the third ion implantation comprises a 4H-SiC single crystal layer with an inclination of 4° in the <11-20> direction.

[0039] Preferably, the implantation dose of the third ion implantation is ≥10×10 15 atom / cm 2 .

[0040] Preferably, the implantation energy of the third ion implantation is ≥80keV.

[0041] Preferably, the implantation angle of the third ion implantation is 5°-20°.

[0042] Preferably, the implantation depth of the third ion implantation is 0.5-1 μm.

[0043] Preferably, the third bonding method includes Ar ion activation.

[0044] Preferably, the bonding strength of the third bonding is > 1.5 J / m 2 .

[0045] Preferably, the temperature of the third peeling is 150-300°C.

[0046] Preferably, the third peeling time is 30-45 minutes.

[0047] Preferably, the surface roughness Ra of the bonded composite substrate obtained after the third polishing is less than 0.2 nm.

[0048] In a third aspect, the present invention provides an epitaxial structure, comprising the bonded composite substrate as described in the first aspect.

[0049] As a preferred technical solution of the present invention, the epitaxial structure comprises, from bottom to top:

[0050] The composite substrate, the buffer layer, the first N-type 4H-SiC layer, the second N-type 4H-SiC layer, the first P-type 3C-SiC layer and the second P-type 3C-SiC layer are bonded.

[0051] In a fourth aspect, the present invention provides a method for preparing the epitaxial structure according to the third aspect, the preparation method comprising:

[0052] The bonded composite substrate is sequentially etched, a buffer layer is grown, a first N-type 4H-SiC layer is grown, a second N-type 4H-SiC layer is grown, a first P-type 3C-SiC layer is grown, and a second P-type 3C-SiC layer is grown to obtain an epitaxial structure.

[0053] As a preferred technical solution of the present invention, the flow rate of the carrier gas used in the etching is 100-500slm.

[0054] Preferably, the flow rate of the carbon source gas used in the etching is 10-20 sccm.

[0055] Preferably, the etching temperature is 1520-1580°C.

[0056] Preferably, the etching pressure is 50-100 mbar.

[0057] Preferably, the etching time is 1-2 minutes.

[0058] Preferably, the flow rate of the carrier gas used in the growth of the buffer layer is 100-500 slm.

[0059] Preferably, the flow rate of the silicon source gas used in the growth of the buffer layer is 50-100 scmm.

[0060] Preferably, the flow rate of the carbon source gas used in the growth of the buffer layer is 30-80 sccm.

[0061] Preferably, the flow rate of the N-type dopant used in the growth of the buffer layer is 20-30 sccm.

[0062] Preferably, the growth temperature of the buffer layer is 1520-1580°C.

[0063] Preferably, the growth pressure of the buffer layer is 50-100 mbar.

[0064] Preferably, the thickness of the buffer layer obtained by growing the buffer layer is 0.5-2 μm.

[0065] Preferably, the doping concentration of the buffer layer obtained by growing the buffer layer is 1×10 17 -2×10 18 atom / cm 3 .

[0066] Preferably, the flow rate of the carrier gas used in the growth of the first N-type 4H-SiC layer is 100-500 slm.

[0067] Preferably, the flow rate of the silicon source gas used in the growth of the first N-type 4H-SiC layer is 300-600 scmm.

[0068] Preferably, the flow rate of the carbon source gas used in the growth of the first N-type 4H-SiC layer is 400-600 sccm.

[0069] Preferably, the flow rate of the N-type dopant used in the growth of the first N-type 4H-SiC layer is 5-10 sccm.

[0070] Preferably, the growth temperature of the first N-type 4H-SiC layer is 1520-1580°C.

[0071] Preferably, the growth pressure of the first N-type 4H-SiC layer is 50-100 mbar.

[0072] Preferably, the thickness of the N-type 4H-SiC layer obtained by growing the first N-type 4H-SiC layer is 5-30 μm.

[0073] Preferably, the doping concentration of the N-type 4H-SiC layer obtained by growing the first N-type 4H-SiC layer is 0.5×10 16 -2×10 16 atom / cm 3 .

[0074] Preferably, the flow rate of the carrier gas used in the growth of the second N-type 4H-SiC layer is 100-500 slm.

[0075] Preferably, the flow rate of the silicon source gas used in the growth of the second N-type 4H-SiC layer is 300-600 scmm.

[0076] Preferably, the flow rate of the carbon source gas used in the growth of the second N-type 4H-SiC layer is 400-600 sccm.

[0077] Preferably, the flow rate of the N-type dopant used in the growth of the second N-type 4H-SiC layer is 5-10 sccm.

[0078] Preferably, the growth temperature of the second N-type 4H-SiC layer is 1520-1580°C.

[0079] Preferably, the growth pressure of the second N-type 4H-SiC layer is 50-100 mbar.

[0080] Preferably, the thickness of the N-type 4H-SiC layer obtained by growing the second N-type 4H-SiC layer is 0.5-2 μm.

[0081] Preferably, the doping concentration of the N-type 4H-SiC layer obtained by growing the second N-type 4H-SiC layer is 2×10 16 -4×10 16 atom / cm 3 .

[0082] Preferably, the flow rate of the carrier gas used in the growth of the first P-type 3C-SiC layer is 100-500 slm.

[0083] Preferably, the flow rate of the silicon source gas used in the growth of the first P-type 3C-SiC layer is 400-800 scmm.

[0084] Preferably, the flow rate of the carbon source gas used in the growth of the first P-type 3C-SiC layer is 400-800 sccm.

[0085] Preferably, the flow rate of the P-type dopant used in the growth of the first P-type 3C-SiC layer is 5-10 sccm.

[0086] Preferably, the growth temperature of the first P-type 3C-SiC layer is 1350-1400°C.

[0087] Preferably, the growth pressure of the first P-type 3C-SiC layer is 50-100 mbar.

[0088] Preferably, the growth rate of the first P-type 3C-SiC layer is 1-2 μm / h.

[0089] Preferably, the thickness of the P-type 3C-SiC layer obtained by growing the first P-type 3C-SiC layer is 0.5-1 μm.

[0090] Preferably, the doping concentration of the P-type 3C-SiC layer obtained by growing the first P-type 3C-SiC layer is 1×10 16 -2×10 16 atom / cm 3 .

[0091] Preferably, the flow rate of the carrier gas used in the growth of the second P-type 3C-SiC layer is 100-500 slm.

[0092] Preferably, the flow rate of the silicon source gas used in the growth of the second P-type 3C-SiC layer is 400-800 scmm.

[0093] Preferably, the flow rate of the carbon source gas used in the growth of the second P-type 3C-SiC layer is 400-800 sccm.

[0094] Preferably, the flow rate of the P-type dopant used in the growth of the second P-type 3C-SiC layer is 50-80 sccm.

[0095] Preferably, the growth temperature of the second P-type 3C-SiC layer is 1350-1400°C.

[0096] Preferably, the growth pressure of the second P-type 3C-SiC layer is 50-100 mbar.

[0097] Preferably, the growth rate of the second P-type 3C-SiC layer is 1-2 μm / h.

[0098] Preferably, the thickness of the P-type 3C-SiC layer obtained by growing the second P-type 3C-SiC layer is 0.5-2 μm.

[0099] Preferably, the doping concentration of the P-type 3C-SiC layer obtained by growing the second P-type 3C-SiC layer is 1×10 17 -5×10 17 atom / cm 3 .

[0100] In a fifth aspect, the present invention provides a power device, comprising the bonded composite substrate as described in the first aspect.

[0101] Compared with the prior art solutions, the present invention has the following beneficial effects:

[0102] (1) During the bonding process of the bonded composite substrate provided by the present invention, high-speed Ar ions or Ar atoms continuously bombard the silicon carbide wafer, and dense atomic collisions occur inside the silicon carbide crystal, opening more dangling bonds, and then the single crystal donor material injection surface is bonded to the polycrystalline support sheet. Through H ion injection, H2 is formed during the annealing process, and the gas pressure increases. Through low-temperature annealing treatment, the injected ions are aggregated to form a foaming layer, and the pressure of the bubbles in the foaming layer causes the single crystal donor material to crack from the foaming layer to achieve the purpose of single crystal transfer, and a single crystal material without an insulating layer, higher quality and thinner film thickness can be obtained.

[0103] (2) The bonded composite substrate provided by the present invention is targeted at polycrystalline SiC substrates with high doping concentration and N-heavy doping. The higher the doping concentration, the more stacking faults there are, and the stacking faults will expand in the substrate. The driving force for the expansion of the stacking faults is the quantum well mechanism. The band gap difference between 3C-SiC and 4H-SiC is 0.9eV, so a quantum well is formed. The driving force for the expansion of the stacking faults is the quantum well mechanism. By forming a quantum well at the bonding interface, the stacking faults are expanded to the bonding interface, thereby preventing the stacking faults from expanding to the single crystal layer or even the epitaxial layer, thereby improving the device's withstand voltage performance. The breakdown voltage of the device obtained by using the specific substrate and epitaxial structure of the present invention is ≥1657V. When the specific substrate of the present invention is used, the breakdown voltage of the obtained device is ≥1589V.

[0104] (3) The single crystal layer of the existing bonding substrate is relatively thin. It is easy to etch through the single crystal layer under H2 etching conditions during conventional silicon carbide epitaxial growth because the surface free energy is 123 kJ / mol in a pure H2 atmosphere. However, the surface free energy of the bonding composite substrate provided by the present invention is 207 kJ / mol in a H2 / SiH4 atmosphere and 117.6 kJ / mol in a H2 / C3H8 atmosphere. That is, the bonding substrate of the present invention can reduce the surface free energy when etched in a H2 / C3H8 atmosphere, thereby preventing the thin single crystal layer from being etched through. BRIEF DESCRIPTION OF THE DRAWINGS

[0105] Figure 1 is a schematic diagram of a bonding composite substrate provided by an embodiment of the present invention;

[0106] Figure 2 It is a schematic diagram of an epitaxial structure provided by an embodiment of the present invention.

[0107] In the figure: 1, polycrystalline SiC layer, 2, first 4H-SiC layer, 3, 3C-SiC layer, 4, first 4H-SiC layer;

[0108] 100. Bonded composite substrate, 200. Buffer layer, 300. First N-type 4H-SiC layer, 400. Second N-type 4H-SiC layer, 500. First P-type 3C-SiC layer, 600. Second P-type 3C-SiC layer.

[0109] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims. DETAILED DESCRIPTION

[0110] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:

[0111] This embodiment provides a bonded composite substrate, such as Figure 1 As shown, the bonded composite substrate comprises: a polycrystalline SiC layer 1, a first 4H-SiC layer 2, a 3C-SiC layer 3 and a second 4H-SiC layer 4 bonded in sequence.

[0112] The thickness of the polycrystalline SiC layer 1 is 330-370 μm, for example, 330 μm, 335 μm, 340 μm, 345 μm, 350 μm, 355 μm, 360 μm, 365 μm or 370 μm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0113] Among them, the thickness of the first 4H-SiC layer 2 is 0.3-0.7μm, for example, it can be 0.3μm, 0.35μm, 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm, 0.65μm or 0.7μm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0114] The thickness of the 3C-SiC layer 3 is 0.3-0.7 μm, for example, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm or 0.7 μm, but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0115] The thickness of the second 4H-SiC layer 4 is 0.3-0.7 μm, for example, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm or 0.7 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0116] Furthermore, the present invention provides a method for preparing the aforementioned bonded composite substrate, the method comprising:

[0117] Performing a first bonding between the 4H-SiC layer implanted with the first ions and the polycrystalline SiC layer, followed by a first stripping and a first polishing to obtain a first bonding body;

[0118] Performing a second bonding between the first bonding body and the 3C-SiC layer implanted with the second ions, and then performing a second peeling and a second polishing to obtain a second bonding body;

[0119] The second bonding body and the 4H-SiC layer that has been subjected to the third ion implantation are subjected to the third bonding, and then subjected to the third stripping and polishing to obtain a bonded composite substrate.

[0120] In the present invention, the polycrystalline SiC layer 1, the first 4H-SiC layer 2, the 3C-SiC layer 3, and the second 4H-SiC layer 4 used in the bonding process can be optionally subjected to appearance inspection, such as ensuring: no edge cracks; the cumulative area of ​​hexagonal voids is less than 0.05%; no polymorphism; the cumulative area of ​​visual inclusions is less than 0.05%; no scratches; no edge collapse with a length or width of ≥0.2mm is allowed; no contaminants on the surface; surface roughness Ra<0.3nm, Rmax<3nm; surface parameters-LTV≤2.5μm, TTV≤6um, Bo≤25μm, Warp≤35μm.

[0121] The 4H-SiC layer used in the first ion implantation includes an N doping concentration of 5×10 18 -1×10 19 atom / cm 3 , 4H-SiC single crystal layer with a 4° angle in the <11-20> direction, for example, can be 5×10 18 atom / cm 3 , 5.5×10 18 atom / cm 3 , 6×1018 atom / cm 3 , 6.5×10 18 atom / cm 3 ,7×10 18 atom / cm 3 , 7.5×10 18 atom / cm 3 , 8×10 18 atom / cm 3 , 8.5×10 18 atom / cm 3 ,9×10 18 atom / cm 3 , 9.5×10 18 atom / cm 3 or 1×10 19 atom / cm 3 The above values ​​are not limited to the above values. Other values ​​not listed in the above values ​​also meet the requirements.

[0122] In the present invention, tom / cm 3 Refers to the number of atoms contained in a unit volume.

[0123] The implantation dose of the first ion implantation is ≥10×10 15 atom / cm 2 , for example, it can be 10×10 15 atom / cm 2 , 12×10 15 atom / cm 2 , 14×10 15 atom / cm 2 , 16×10 15 atom / cm 2 , 18×10 15 atom / cm 2 or 20×10 15 atom / cm 2 The above values ​​are not limited to the above values. Other values ​​not listed in the above values ​​also meet the requirements.

[0124] In the present invention, atom / cm 2 Refers to the number of atoms contained in a unit area.

[0125] Among them, the injection energy of the first ion injection is ≥80keV, for example, it can be 80keV, 85keV, 90keV, 95keV, 100keV, 105keV, 110keV, 120keV or 150keV, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0126] Among them, the injection angle of the first ion injection is 5°-20°, for example, it can be 5°, 6°, 8°, 10°, 12°, 14°, 16°, 18° or 20°, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0127] The implantation depth of the first ion implantation is 0.5-1 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0128] Wherein, the first bonding method includes Ar ion activation.

[0129] Wherein, the bonding strength of the first bonding is greater than 1.5 J / m 2 , for example, it can be 1.6 J / m 2 , 1.8J / m 2 , 2J / m 2 , 2.2J / m 2 , 2.4J / m 2 , 2.6J / m 2 , 2.8J / m 2 or 3J / m 2 The above values ​​are not limited to the above values. Other values ​​not listed in the above values ​​also meet the requirements.

[0130] Among them, the temperature of the first peeling is 150-300℃, for example, it can be 150℃, 160℃, 180℃, 200℃, 220℃, 240℃, 260℃, 280℃ or 300℃, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0131] Among them, the time of the first peeling is 30-45min, for example, it can be 30min, 32min, 34min, 36min, 38min, 40min, 42min, 44min or 45min, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0132] Among them, the surface roughness of the first bonding body obtained after the first polishing is Ra<0.2nm, for example, it can be 0.19nm, 0.18nm, 0.16nm, 0.14nm, 0.12nm, 0.1nm, 0.08nm, 0.06nm, 0.04nm, 0.02nm or 0.01nm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0133] The 3C-SiC layer used in the second ion implantation includes a 3C-SiC single crystal layer with a 4° inclination in the <11-20> direction.

[0134] Wherein, the implantation dose of the second ion implantation is ≥10×10 15 atom / cm 2 , for example, it can be 10×10 15 atom / cm 2 , 12×10 15 atom / cm 2 , 14×10 15 atom / cm 2 , 16×10 15 atom / cm 2 , 18×10 15 atom / cm 2 or 20×10 15 atom / cm 2 The above values ​​are not limited to the above values. Other values ​​not listed in the above values ​​also meet the requirements.

[0135] Among them, the injection energy of the second ion injection is ≥80keV, for example, it can be 80keV, 85keV, 90keV, 95keV, 100keV, 105keV, 110keV, 120keV or 150keV, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0136] Among them, the injection angle of the second ion injection is 5°-20°, for example, it can be 5°, 6°, 8°, 10°, 12°, 14°, 16°, 18° or 20°, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0137] The implantation depth of the second ion implantation is 0.5-1 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm, but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0138] Wherein, the second bonding method includes Ar ion activation.

[0139] Wherein, the bonding strength of the second bonding is greater than 1.5 J / m 2 , for example, it can be 1.6 J / m 2 , 1.8J / m 2 , 2J / m 2 , 2.2J / m 2 , 2.4J / m 2 , 2.6J / m2 , 2.8J / m 2 or 3J / m 2 The above values ​​are not limited to the above values. Other values ​​not listed in the above values ​​also meet the requirements.

[0140] Among them, the temperature of the second peeling is 150-300℃, for example, it can be 150℃, 160℃, 180℃, 200℃, 220℃, 240℃, 260℃, 280℃ or 300℃, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0141] Among them, the time of the second peeling is 30-45min, for example, it can be 30min, 32min, 34min, 36min, 38min, 40min, 42min, 44min or 45min, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0142] Among them, the surface roughness Ra of the second bonding body obtained after the second polishing is less than 0.2nm, for example, it can be 0.19nm, 0.18nm, 0.16nm, 0.14nm, 0.12nm, 0.1nm, 0.08nm, 0.06nm, 0.04nm, 0.02nm or 0.01nm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0143] The 4H-SiC layer used in the third ion implantation includes a 4H-SiC single crystal layer with a 4° inclination in the <11-20> direction.

[0144] The implantation dose of the third ion implantation is ≥10×10 15 atom / cm 2 , for example, it can be 10×10 15 atom / cm 2 , 12×10 15 atom / cm 2 , 14×10 15 atom / cm 2 , 16×10 15 atom / cm 2 , 18×10 15 atom / cm 2 or 20×10 15 atom / cm 2 The above values ​​are not limited to the above values. Other values ​​not listed in the above values ​​also meet the requirements.

[0145] Among them, the injection energy of the third ion injection is ≥80keV, for example, it can be 80keV, 85keV, 90keV, 95keV, 100keV, 105keV, 110keV, 120keV or 150keV, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0146] Among them, the injection angle of the third ion injection is 5°-20°, for example, it can be 5°, 6°, 8°, 10°, 12°, 14°, 16°, 18° or 20°, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0147] The implantation depth of the third ion implantation is 0.5-1 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm, but is not limited to the listed values, and other values ​​not listed in the range also meet the requirements.

[0148] Wherein, the third bonding method includes Ar ion activation.

[0149] Wherein, the bonding strength of the third bonding is > 1.5 J / m 2 , for example, it can be 1.6 J / m 2 , 1.8J / m 2 , 2J / m 2 , 2.2J / m 2 , 2.4J / m 2 , 2.6J / m 2 , 2.8J / m 2 or 3J / m 2 The above values ​​are not limited to the above values. Other values ​​not listed in the above values ​​also meet the requirements.

[0150] Among them, the temperature of the third peeling is 150-300℃, for example, it can be 150℃, 160℃, 180℃, 200℃, 220℃, 240℃, 260℃, 280℃ or 300℃, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0151] Among them, the time of the third peeling is 30-45 minutes, for example, it can be 30 minutes, 32 minutes, 34 minutes, 36 minutes, 38 minutes, 40 minutes, 42 minutes, 44 minutes or 45 minutes, but it is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0152] Among them, the surface roughness Ra of the bonded composite substrate obtained after the third polishing is less than 0.2nm, for example, it can be 0.19nm, 0.18nm, 0.16nm, 0.14nm, 0.12nm, 0.1nm, 0.08nm, 0.06nm, 0.04nm, 0.02nm or 0.01nm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0153] In the present invention, cleaning can be performed selectively before each operation process until the number of particles with a diameter of less than 20 μm on the surface of the cleaning object is less than 10 / piece, so as to avoid the previous operation process from having an adverse effect on the subsequent operation, such as performing at least one RCA standard cleaning.

[0154] In the present invention, the bonding process is carried out using a bonding machine, such as using an Ar ion beam to attack the surface of the single crystal to open dangling bonds, perform surface activation, and then achieve bonding, but it is necessary to ensure that the bonding strength specified in the present invention is achieved.

[0155] Furthermore, the present invention provides an epitaxial structure, which includes the aforementioned bonded composite substrate.

[0156] Wherein, the epitaxial structure, such as Figure 2 As shown, from bottom to top, it includes:

[0157] The bonded composite substrate 100 , the buffer layer 200 , the first N-type 4H—SiC layer 300 , the second N-type 4H—SiC layer 400 , the first P-type 3C—SiC layer 500 , and the second P-type 3C—SiC layer 600 .

[0158] Furthermore, the present invention provides a method for preparing the aforementioned epitaxial structure, the method comprising:

[0159] The bonded composite substrate is sequentially etched, a buffer layer is grown, a first N-type 4H-SiC layer is grown, a second N-type 4H-SiC layer is grown, a first P-type 3C-SiC layer is grown, and a second P-type 3C-SiC layer is grown to obtain an epitaxial structure.

[0160] In the present invention, when preparing the epitaxial structure, the starting surface of the bonding composite substrate 100 is the surface where the second 4H-SiC layer 4 is located, that is, when growing the buffer layer, the buffer layer 200 grows on the surface of the second 4H-SiC layer.

[0161] Among them, the flow rate of the carrier gas used in the etching is 100-500slm, for example, it can be 100slm, 150slm, 200slm, 250slm, 300slm, 350slm, 400slm, 450slm or 500slm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0162] Among them, the flow rate of the carbon source gas used in the etching is 10-20sccm, for example, it can be 10sccm, 12sccm, 14sccm, 16sccm, 18sccm or 20sccm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0163] Among them, the etching temperature is 1520-1580℃, for example, it can be 1520℃, 1525℃, 1530℃, 1535℃, 1540℃, 1545℃, 1550℃, 1555℃, 1560℃, 1565℃, 1570℃, 1575℃ or 1580℃, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0164] The etching pressure is 50-100 mbar, for example, 50 mbar, 55 mbar, 60 mbar, 65 mbar, 70 mbar, 75 mbar, 80 mbar, 85 mbar, 90 mbar, 95 mbar or 100 mbar, etc., but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0165] The etching time is 1-2 minutes, for example, 1 minute, 1.5 minutes or 2 minutes, but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0166] Among them, the flow rate of the carrier gas used in the growth of the buffer layer is 100-500slm, for example, it can be 100slm, 150slm, 200slm, 250slm, 300slm, 350slm, 400slm, 450slm or 500slm, but is not limited to the listed values, and other unlisted values ​​within this range also meet the requirements.

[0167] Among them, the flow rate of the silicon source gas used in the growth of the buffer layer is 50-100scmm, for example, it can be 50sccm, 60sccm, 70sccm, 80sccm, 90sccm or 100sccm, but is not limited to the listed values, and other unlisted values ​​within this range also meet the requirements.

[0168] Among them, the flow rate of the carbon source gas used in the growth of the buffer layer is 30-80sccm, for example, it can be 30sccm, 40sccm, 50sccm, 60sccm, 70sccm or 80sccm, but is not limited to the listed values, and other unlisted values ​​within this range also meet the requirements.

[0169] Among them, the flow rate of the N-type dopant used in the growth of the buffer layer is 20-30sccm, for example, it can be 20sccm, 22sccm, 24sccm, 26sccm, 28sccm or 30sccm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0170] Among them, the growth temperature of the buffer layer is 1520-1580℃, for example, it can be 1520℃, 1525℃, 1530℃, 1535℃, 1540℃, 1545℃, 1550℃, 1555℃, 1560℃, 1565℃, 1570℃, 1575℃ or 1580℃, but is not limited to the listed values. Other unlisted values ​​within the range also meet the requirements.

[0171] Among them, the growth pressure of the buffer layer is 50-100mbar, for example, it can be 50mbar, 55mbar, 60mbar, 65mbar, 70mbar, 75mbar, 80mbar, 85mbar, 90mbar, 95mbar or 100mbar, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0172] The thickness of the buffer layer obtained by growing the buffer layer is 0.5-2μm, for example, it can be 0.5μm, 0.6μm, 0.8μm, 1μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm or 2μm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0173] The doping concentration of the buffer layer obtained by growing the buffer layer is 1×10 17 -2×10 18 atom / cm 3 , for example, it can be 1×10 17 atom / cm 3 , 2×10 17 atom / cm 3 , 4×10 17 atom / cm 3 , 6×10 17 atom / cm 3 , 8×10 17 atom / cm3 , 10×10 17 atom / cm 3 , 12×10 17 atom / cm 3 , 14×10 17 atom / cm 3 , 16×10 17 atom / cm 3 , 18×10 17 atom / cm 3 or 2×10 18 atom / cm 3 The above values ​​are not limited to the above values. Other values ​​not listed in the above values ​​also meet the requirements.

[0174] Among them, the flow rate of the carrier gas used in the growth of the first N-type 4H-SiC layer is 100-500slm, for example, it can be 100slm, 150slm, 200slm, 250slm, 300slm, 350slm, 400slm, 450slm or 500slm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0175] Among them, the flow rate of the silicon source gas used in the growth of the first N-type 4H-SiC layer is 300-600scmm, for example, it can be 300sccm, 350sccm, 400sccm, 450sccm, 500sccm, 550sccm or 600sccm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0176] Among them, the flow rate of the carbon source gas used in the growth of the first N-type 4H-SiC layer is 400-600sccm, for example, it can be 400sccm, 420sccm, 440sccm, 460sccm, 580sccm, 500sccm, 520sccm, 540sccm, 560sccm, 580sccm or 600sccm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0177] Among them, the flow rate of the N-type dopant used in the growth of the first N-type 4H-SiC layer is 5-10sccm, for example, it can be 5sccm, 6sccm, 7sccm, 8sccm, 9sccm or 10sccm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0178] Among them, the growth temperature of the first N-type 4H-SiC layer is 1520-1580°C, for example, it can be 1520°C, 1525°C, 1530°C, 1535°C, 1540°C, 1545°C, 1550°C, 1555°C, 1560°C, 1565°C, 1570°C, 1575°C or 1580°C, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0179] Among them, the growth pressure of the first N-type 4H-SiC layer is 50-100mbar, for example, it can be 50mbar, 55mbar, 60mbar, 65mbar, 70mbar, 75mbar, 80mbar, 85mbar, 90mbar, 95mbar or 100mbar, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0180] Among them, the thickness of the N-type 4H-SiC layer obtained by growing the first N-type 4H-SiC layer is 5-30μm, for example, it can be 5μm, 6μm, 7μm, 8μm, 10μm, 15μm, 20μm, 25μm or 30μm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0181] The doping concentration of the N-type 4H-SiC layer obtained by growing the first N-type 4H-SiC layer is 0.5×10 16 -2×10 16 atom / cm 3 , for example, it can be 0.5×10 16 atom / cm 3 , 0.6×10 16 atom / cm 3 , 0.8×10 16 atom / cm 3 , 1×10 16 atom / cm 3 , 1.2×10 16 atom / cm 3 , 1.4×10 16 atom / cm 3 , 1.8×10 16 atom / cm 3 or 2×10 16 atom / cm 3 The above values ​​are not limited to the above values. Other values ​​not listed in the above values ​​also meet the requirements.

[0182] Among them, the flow rate of the carrier gas used in the growth of the second N-type 4H-SiC layer is 100-500slm, for example, it can be 100slm, 150slm, 200slm, 250slm, 300slm, 350slm, 400slm, 450slm or 500slm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0183] Among them, the flow rate of the silicon source gas used in the growth of the second N-type 4H-SiC layer is 300-600scmm, for example, it can be 300sccm, 350sccm, 400sccm, 450sccm, 500sccm, 550sccm or 600sccm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0184] Among them, the flow rate of the carbon source gas used in the growth of the second N-type 4H-SiC layer is 400-600sccm, for example, it can be 400sccm, 420sccm, 440sccm, 460sccm, 580sccm, 500sccm, 520sccm, 540sccm, 560sccm, 580sccm or 600sccm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0185] Among them, the flow rate of the N-type dopant used in the growth of the second N-type 4H-SiC layer is 5-10sccm, for example, it can be 5sccm, 6sccm, 7sccm, 8sccm, 9sccm or 10sccm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0186] Among them, the growth temperature of the second N-type 4H-SiC layer is 1520-1580°C, for example, it can be 1520°C, 1525°C, 1530°C, 1535°C, 1540°C, 1545°C, 1550°C, 1555°C, 1560°C, 1565°C, 1570°C, 1575°C or 1580°C, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0187] Among them, the growth pressure of the second N-type 4H-SiC layer is 50-100mbar, for example, it can be 50mbar, 55mbar, 60mbar, 65mbar, 70mbar, 75mbar, 80mbar, 85mbar, 90mbar, 95mbar or 100mbar, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0188] Among them, the thickness of the N-type 4H-SiC layer obtained by growing the second N-type 4H-SiC layer is 0.5-2μm, for example, it can be 0.5μm, 0.6μm, 0.8μm, 1μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm or 2μm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0189] The doping concentration of the N-type 4H-SiC layer obtained by growing the second N-type 4H-SiC layer is 2×10 16 -4×10 16 atom / cm 3 , for example, it can be 2×10 16 atom / cm 3 , 2.5×10 16 atom / cm 3 , 3×10 16 atom / cm 3 , 3.5×10 16 atom / cm 3 or 4×10 16 atom / cm 3 The above values ​​are not limited to the above values. Other values ​​not listed in the above values ​​also meet the requirements.

[0190] Among them, the flow rate of the carrier gas used in the growth of the first P-type 3C-SiC layer is 100-500slm, for example, it can be 100slm, 150slm, 200slm, 250slm, 300slm, 350slm, 400slm, 450slm or 500slm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0191] Among them, the flow rate of the silicon source gas used in the growth of the first P-type 3C-SiC layer is 400-800scmm, for example, it can be 400sccm, 450sccm, 500sccm, 550sccm, 600sccm, 650sccm, 700sccm, 750sccm or 800sccm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0192] Among them, the flow rate of the carbon source gas used in the growth of the first P-type 3C-SiC layer is 400-800sccm, for example, it can be 400sccm, 450sccm, 500sccm, 550sccm, 600sccm, 650sccm, 700sccm, 750sccm or 800sccm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0193] Among them, the flow rate of the P-type dopant used in the growth of the first P-type 3C-SiC layer is 5-10sccm, for example, it can be 5sccm, 6sccm, 7sccm, 8sccm, 9sccm or 10sccm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0194] Among them, the growth temperature of the first P-type 3C-SiC layer is 1350-1400°C, for example, it can be 1350°C, 1360°C, 1370°C, 1380°C, 1390°C or 1400°C, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0195] Among them, the growth pressure of the first P-type 3C-SiC layer is 50-100mbar, for example, it can be 50mbar, 55mbar, 60mbar, 65mbar, 70mbar, 75mbar, 80mbar, 85mbar, 90mbar, 95mbar or 100mbar, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0196] Among them, the growth rate of the first P-type 3C-SiC layer is 1-2μm / h, for example, it can be 1μm / h, 1.2μm / h, 1.4μm / h, 1.6μm / h, 1.8μm / h or 2μm / h, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0197] Among them, the thickness of the P-type 3C-SiC layer obtained by growing the first P-type 3C-SiC layer is 0.5-1μm, for example, it can be 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm or 1μm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0198] The doping concentration of the P-type 3C-SiC layer obtained by growing the first P-type 3C-SiC layer is 1×10 16 -2×10 16 atom / cm 3 , for example, it can be 1×10 16 atom / cm 3 , 1.2×10 16 atom / cm 3 , 1.4×10 16 atom / cm 3 , 1.6×10 16 atom / cm 3 , 1.8×10 16atom / cm 3 or 2×10 16 atom / cm 3 The above values ​​are not limited to the above values. Other values ​​not listed in the above values ​​also meet the requirements.

[0199] Among them, the flow rate of the carrier gas used in the growth of the second P-type 3C-SiC layer is 100-500slm, for example, it can be 100slm, 150slm, 200slm, 250slm, 300slm, 350slm, 400slm, 450slm or 500slm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0200] Among them, the flow rate of the silicon source gas used in the growth of the second P-type 3C-SiC layer is 400-800scmm, for example, it can be 400sccm, 450sccm, 500sccm, 550sccm, 600sccm, 650sccm, 700sccm, 750sccm or 800sccm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0201] Among them, the flow rate of the carbon source gas used in the growth of the second P-type 3C-SiC layer is 400-800sccm, for example, it can be 400sccm, 450sccm, 500sccm, 550sccm, 600sccm, 650sccm, 700sccm, 750sccm or 800sccm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0202] Among them, the flow rate of the P-type dopant used in the growth of the second P-type 3C-SiC layer is 50-80sccm, for example, it can be 50sccm, 55sccm, 60sccm, 65sccm, 70sccm, 75sccm or 80sccm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0203] Among them, the growth temperature of the second P-type 3C-SiC layer is 1350-1400°C, for example, it can be 1350°C, 1360°C, 1370°C, 1380°C, 1390°C or 1400°C, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0204] Among them, the growth pressure of the second P-type 3C-SiC layer is 50-100mbar, for example, it can be 50mbar, 55mbar, 60mbar, 65mbar, 70mbar, 75mbar, 80mbar, 85mbar, 90mbar, 95mbar or 100mbar, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0205] Among them, the growth rate of the second P-type 3C-SiC layer is 1-2μm / h, for example, it can be 1μm / h, 1.2μm / h, 1.4μm / h, 1.6μm / h, 1.8μm / h or 2μm / h, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0206] Among them, the thickness of the P-type 3C-SiC layer obtained by growing the second P-type 3C-SiC layer is 0.5-2μm, for example, it can be 0.5μm, 0.6μm, 0.8μm, 1μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm or 2μm, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0207] The doping concentration of the P-type 3C-SiC layer obtained by growing the second P-type 3C-SiC layer is 1×10 17 -5×10 17 atom / cm 3 , for example, it can be 1×10 16 atom / cm 3 , 2×10 16 atom / cm 3 , 3×10 16 atom / cm 3 , 4×10 16 atom / cm 3 or 5×10 16 atom / cm 3 The above values ​​are not limited to the above values. Other values ​​not listed in the above values ​​also meet the requirements.

[0208] In the present invention, the carrier gas used in the preparation of the epitaxial structure includes hydrogen and other commonly used carrier gases in the art.

[0209] In the present invention, the silicon source gas used in the preparation of the epitaxial structure includes commonly used silicon source gases such as SiCl4, SiHCl3, SiH2C12 or SiH3Cl.

[0210] In the present invention, the carbon source gas used in the preparation of the epitaxial structure includes commonly used carbon source gases such as C2H2, C2H4, and C3H8.

[0211] In the present invention, the N-type dopant used in the preparation of the epitaxial structure includes commonly used N-type dopants such as N2 and / or NH3.

[0212] In the present invention, the P-type dopant used in the preparation of the epitaxial structure includes common P-type dopants such as TMAl.

[0213] Further, in order to illustrate the effects that can be achieved by providing a bonded composite substrate according to the present invention, the following practical examples are used for exemplary description, as follows:

[0214] Example 1

[0215] This embodiment provides a bonded composite substrate, the bonded composite substrate comprising: a polycrystalline SiC layer 1, a first 4H-SiC layer 2, a 3C-SiC layer 3, and a second 4H-SiC layer 4 bonded in sequence;

[0216] The thickness of the polycrystalline SiC layer 1 is 350 μm; the thickness of the first 4H-SiC layer 2 is 0.4 μm; the thickness of the 3C-SiC layer 3 is 0.6 μm; and the thickness of the second 4H-SiC layer 4 is 0.5 μm.

[0217] The preparation process is as follows:

[0218] Performing a first bonding between the 4H-SiC layer implanted with the first ions and the polycrystalline SiC layer, followed by a first stripping and a first polishing to obtain a first bonding body;

[0219] Performing a second bonding between the first bonding body and the 3C-SiC layer implanted with the second ions, and then performing a second peeling and a second polishing to obtain a second bonding body;

[0220] The second bonding body and the 4H-SiC layer after the third ion implantation are subjected to a third bonding, followed by a third stripping and polishing to obtain a bonded composite substrate;

[0221] The 4H-SiC layer used in the first ion implantation has an N doping concentration of 6×10 18 atom / cm 3 , 4H-SiC single crystal layer with a 4° orientation of <11-20>; the first ion implantation dosage is 10×10 15 atom / cm 2 The injection energy is 80 keV, the injection angle is 15°, and the injection depth is 0.8 μm; the first bonding method is Ar ion activation, and the bonding strength is 1.8 J / m 2 The temperature of the first peeling is 200°C and the time is 40 min. The surface roughness Ra of the first bonded body obtained after the first polishing is 0.15 nm.

[0222] The 3C-SiC layer used in the second ion implantation is a 3C-SiC single crystal layer with a 4° inclination in the <11-20> direction; the implantation dose of the second ion implantation is 12×10 15 atom / cm 2 The injection energy is 85keV, the injection angle is 15°, and the injection depth is 0.7μm; the second bonding method is Ar ion activation, and the bonding strength is 1.6J / m 2 The temperature of the second peeling is 200°C and the time is 40 min. The surface roughness Ra of the second bonded body obtained after the second polishing is 0.18 nm.

[0223] The 4H-SiC layer used in the third ion implantation is a 4H-SiC single crystal layer with a 4° orientation in the <11-20> direction; the implantation dose of the third ion implantation is 20×10 15 atom / cm 2 The injection energy is 90 keV, the injection angle is 15°, and the injection depth is 0.6 μm; the third bonding method is Ar ion activation, and the bonding strength is 1.8 J / m 2 The temperature of the third peeling is 250°C and the time is 35 min. The surface roughness Ra of the bonded composite substrate obtained after the third polishing is 0.14 nm.

[0224] This embodiment provides an epitaxial structure, which includes, from bottom to top:

[0225] The bonded composite substrate 100 , the buffer layer 200 , the first N-type 4H—SiC layer 300 , the second N-type 4H—SiC layer 400 , the first P-type 3C—SiC layer 500 , and the second P-type 3C—SiC layer 600 .

[0226] The preparation process is as follows:

[0227] The bonded composite substrate is sequentially etched, a buffer layer is grown, a first 4H-SiC layer is grown, a second 4H-SiC layer is grown, a first P-type 3C-SiC layer is grown, and a second P-type 3C-SiC layer is grown to obtain an epitaxial structure;

[0228] The flow rate of the carrier gas used in the etching is 300 slm, the flow rate of the carbon source gas is 15 sccm, the temperature is 1540°C, the pressure is 60 mbar, and the time is 1.5 min;

[0229] The flow rate of the carrier gas used in the growth of the buffer layer is 300 slm, the flow rate of the silicon source gas used is 60 scmm, the flow rate of the carbon source gas used is 40 sccm, the flow rate of the N-type dopant used is 25 sccm, the growth temperature is 1540°C, the growth pressure is 60 mbar, the thickness of the obtained buffer layer is 1 μm, and the doping concentration of the obtained buffer layer is 1.5×10 18 atom / cm 3 ;

[0230] The flow rate of the carrier gas used in the growth of the first N-type 4H-SiC layer is 300 slm, the flow rate of the silicon source gas used is 400 scmm, the flow rate of the carbon source gas used is 500 sccm, the flow rate of the N-type dopant used is 6 sccm, the growth temperature is 1540°C, the growth pressure is 60 mbar, the thickness of the obtained N-type 4H-SiC layer is 10 μm, and the doping concentration of the obtained N-type 4H-SiC layer is 1×10 16 atom / cm 3 ;

[0231] The flow rate of the carrier gas used in the growth of the second N-type 4H-SiC layer is 300 slm, the flow rate of the silicon source gas used is 400 scmm, the flow rate of the carbon source gas used is 500 sccm, the flow rate of the N-type dopant used is 6 sccm, the growth temperature is 1540°C, the growth pressure is 60 mbar, the thickness of the obtained N-type 4H-SiC layer is 1.5 μm, and the doping concentration of the obtained N-type 4H-SiC layer is 3.5×10 16 atom / cm 3 ;

[0232] The flow rate of the carrier gas used in the growth of the first P-type 3C-SiC layer is 300 slm, the flow rate of the silicon source gas used is 600 scmm, the flow rate of the carbon source gas used is 600 sccm, the flow rate of the P-type dopant used is 6 sccm, the growth temperature is 1380°C, the growth pressure is 80 mbar, the growth rate is 1.5 μm / h, the thickness of the obtained P-type 3C-SiC layer is 0.8 μm, and the doping concentration of the obtained P-type 3C-SiC layer is 1.6×10 16 atom / cm 3 ;

[0233] The flow rate of the carrier gas used in the growth of the second P-type 3C-SiC layer is 300 slm, the flow rate of the silicon source gas used is 600 scmm, the flow rate of the carbon source gas used is 600 sccm, the flow rate of the P-type dopant used is 60 sccm, the growth temperature is 1380°C, the growth pressure is 80 mbar, the growth rate is 1.4 μm / h, the thickness of the obtained P-type 3C-SiC layer is 1.5 μm, and the doping concentration of the obtained P-type 3C-SiC layer is 4×10 17atom / cm 3 ;

[0234] In this embodiment, the carrier gas used is hydrogen, the silicon source gas used is SiCl4, the carbon source gas used is C2H2, the N-type dopant used is N2, and the P-type dopant used is TMAl.

[0235] Example 2

[0236] This embodiment provides a bonded composite substrate, the bonded composite substrate comprising: a polycrystalline SiC layer 1, a first 4H-SiC layer 2, a 3C-SiC layer 3, and a second 4H-SiC layer 4 bonded in sequence;

[0237] The thickness of the polycrystalline SiC layer is 360 μm; the thickness of the first 4H-SiC layer is 0.5 μm; the thickness of the 3C-SiC layer is 0.5 μm; and the thickness of the second 4H-SiC layer is 0.6 μm.

[0238] The preparation process is as follows:

[0239] Performing a first bonding between the 4H-SiC layer implanted with the first ions and the polycrystalline SiC layer, followed by a first stripping and a first polishing to obtain a first bonding body;

[0240] Performing a second bonding between the first bonding body and the 3C-SiC layer implanted with the second ions, and then performing a second peeling and a second polishing to obtain a second bonding body;

[0241] The second bonding body and the 4H-SiC layer after the third ion implantation are subjected to a third bonding, followed by a third stripping and polishing to obtain a bonded composite substrate;

[0242] The 4H-SiC layer used in the first ion implantation includes an N doping concentration of 8×10 18 atom / cm 3 , 4H-SiC single crystal layer with a 4° angle in the <11-20> direction; the first ion implantation dosage is 12×10 15 atom / cm 2 The injection energy is 85keV, the injection angle is 10°, and the injection depth is 0.7μm; the first bonding method is Ar ion activation, and the bonding strength is 2J / m 2 The temperature of the first peeling is 250°C and the time is 35 min. The surface roughness Ra of the first bonded body obtained after the first polishing is 0.13 nm.

[0243] The 3C-SiC layer used in the second ion implantation is a 3C-SiC single crystal layer with a 4° inclination in the <11-20> direction; the implantation dose of the second ion implantation is 14×10 15 atom / cm2 The injection energy is 80 keV, the injection angle is 10°, and the injection depth is 0.8 μm; the second bonding method is Ar ion activation, and the bonding strength is 1.8 J / m 2 The temperature of the second peeling is 250°C and the time is 35 min. The surface roughness Ra of the second bonded body obtained after the second polishing is 0.19 nm.

[0244] The 4H-SiC layer used in the third ion implantation is a 4H-SiC single crystal layer with a 4° orientation in the <11-20> direction; the implantation dose of the third ion implantation is 25×10 15 atom / cm 2 The injection energy is 80 keV, the injection angle is 10°, and the injection depth is 0.7 μm; the third bonding method is Ar ion activation, and the bonding strength is 2.5 J / m 2 The temperature of the third peeling is 200°C and the time is 40 min; the surface roughness Ra of the bonded composite substrate obtained after the third polishing is 0.12 nm.

[0245] This embodiment provides an epitaxial structure, which includes, from bottom to top:

[0246] The bonded composite substrate 100 , the buffer layer 200 , the first N-type 4H—SiC layer 300 , the second N-type 4H—SiC layer 400 , the first P-type 3C—SiC layer 500 , and the second P-type 3C—SiC layer 600 .

[0247] The preparation process is as follows:

[0248] The bonded composite substrate is sequentially etched, a buffer layer is grown, a first 4H-SiC layer is grown, a second 4H-SiC layer is grown, a first P-type 3C-SiC layer is grown, and a second P-type 3C-SiC layer is grown to obtain an epitaxial structure;

[0249] The flow rate of the carrier gas used in the etching is 200 slm, the flow rate of the carbon source gas is 18 sccm, the temperature is 1560°C, the pressure is 80 mbar, and the time is 1.5 min;

[0250] The flow rate of the carrier gas used in the growth of the buffer layer is 200 slm, the flow rate of the silicon source gas used is 80 scmm, the flow rate of the carbon source gas used is 60 sccm, the flow rate of the N-type dopant used is 25 sccm, the growth temperature is 1560°C, the growth pressure is 80 mbar, the thickness of the obtained buffer layer is 1.5 μm, and the doping concentration of the obtained buffer layer is 1.8×10 18 atom / cm 3 ;

[0251] The flow rate of the carrier gas used in the growth of the first N-type 4H-SiC layer is 200 slm, the flow rate of the silicon source gas used is 500 scmm, the flow rate of the carbon source gas used is 550 sccm, the flow rate of the N-type dopant used is 8 sccm, the growth temperature is 1560°C, the growth pressure is 80 mbar, the thickness of the obtained N-type 4H-SiC layer is 20 μm, and the doping concentration of the obtained N-type 4H-SiC layer is 1.5×10 16 atom / cm 3 ;

[0252] The flow rate of the carrier gas used in the growth of the second N-type 4H-SiC layer is 200 slm, the flow rate of the silicon source gas used is 500 scmm, the flow rate of the carbon source gas used is 550 sccm, the flow rate of the N-type dopant used is 8 sccm, the growth temperature is 1560°C, the growth pressure is 80 mbar, the thickness of the obtained N-type 4H-SiC layer is 1 μm, and the doping concentration of the obtained N-type 4H-SiC layer is 3×10 16 atom / cm 3 ;

[0253] The flow rate of the carrier gas used in the growth of the first P-type 3C-SiC layer is 200 slm, the flow rate of the silicon source gas used is 500 scmm, the flow rate of the carbon source gas used is 500 sccm, the flow rate of the P-type dopant used is 8 sccm, the growth temperature is 1360°C, the growth pressure is 60 mbar, the growth rate is 1.5 μm / h, the thickness of the obtained P-type 3C-SiC layer is 0.6 μm, and the doping concentration of the obtained P-type 3C-SiC layer is 1.4×10 16 atom / cm 3 ;

[0254] The flow rate of the carrier gas used in the growth of the second P-type 3C-SiC layer is 200 slm, the flow rate of the silicon source gas used is 500 scmm, the flow rate of the carbon source gas used is 500 sccm, the flow rate of the P-type dopant used is 70 sccm, the growth temperature is 1360°C, the growth pressure is 60 mbar, the growth rate is 1.6 μm / h, the thickness of the obtained P-type 3C-SiC layer is 1 μm, and the doping concentration of the obtained P-type 3C-SiC layer is 2×10 17 atom / cm 3 ;

[0255] In this embodiment, the carrier gas used is hydrogen, the silicon source gas used is SiH3Cl, the carbon source gas used is C3H8, the N-type dopant used is NH3, and the P-type dopant used is TMAl.

[0256] Example 3

[0257] This embodiment provides a bonded composite substrate, the bonded composite substrate comprising: a polycrystalline SiC layer 1, a first 4H-SiC layer 2, a 3C-SiC layer 3, and a second 4H-SiC layer 4 bonded in sequence;

[0258] The thickness of the polycrystalline SiC layer 1 is 330 μm; the thickness of the first 4H-SiC layer 2 is 0.3 μm; the thickness of the 3C-SiC layer 3 is 0.7 μm; and the thickness of the second 4H-SiC layer 4 is 0.3 μm.

[0259] The preparation process is as follows:

[0260] Performing a first bonding between the 4H-SiC layer implanted with the first ions and the polycrystalline SiC layer, followed by a first stripping and a first polishing to obtain a first bonding body;

[0261] Performing a second bonding between the first bonding body and the 3C-SiC layer implanted with the second ions, and then performing a second peeling and a second polishing to obtain a second bonding body;

[0262] The second bonding body and the 4H-SiC layer after the third ion implantation are subjected to a third bonding, followed by a third stripping and polishing to obtain a bonded composite substrate;

[0263] The 4H-SiC layer used in the first ion implantation has an N doping concentration of 5×10 18 atom / cm 3 , 4H-SiC single crystal layer with a 4° orientation of <11-20>; the first ion implantation dosage is 10×10 15 atom / cm 2 The injection energy is 80 keV, the injection angle is 5°, and the injection depth is 0.5 μm; the first bonding method is Ar ion activation, and the bonding strength is 2.5 J / m 2 ; The temperature of the first peeling is 300°C and the time is 30 min; the surface roughness Ra of the first bonded body obtained after the first polishing is 0.12 nm;

[0264] The 3C-SiC layer used in the second ion implantation is a 3C-SiC single crystal layer with a 4° inclination in the <11-20> direction; the implantation dose of the second ion implantation is 12×10 15 atom / cm 2 The injection energy is 85keV, the injection angle is 20°, and the injection depth is 1μm; the second bonding method is Ar ion activation, and the bonding strength is 1.65J / m 2 The second peeling temperature is 150°C and the time is 45 min. The surface roughness Ra of the second bonded body obtained after the second polishing is 0.02 nm.

[0265] The 4H-SiC layer used in the third ion implantation is a 4H-SiC single crystal layer with a 4° orientation in the <11-20> direction; the implantation dose of the third ion implantation is 20×10 15 atom / cm 2 The injection energy is 80 keV, the injection angle is 5°, and the injection depth is 1 μm; the third bonding method is Ar ion activation, and the bonding strength is 1.88 J / m 2 The temperature of the third peeling is 150°C and the time is 45 min; the surface roughness Ra of the bonded composite substrate obtained after the third polishing is 0.04 nm.

[0266] This embodiment provides an epitaxial structure, which includes, from bottom to top:

[0267] The bonded composite substrate 100 , the buffer layer 200 , the first N-type 4H—SiC layer 300 , the second N-type 4H—SiC layer 400 , the first P-type 3C—SiC layer 500 , and the second P-type 3C—SiC layer 600 .

[0268] The preparation process is as follows:

[0269] The bonded composite substrate is sequentially etched, a buffer layer is grown, a first 4H-SiC layer is grown, a second 4H-SiC layer is grown, a first P-type 3C-SiC layer is grown, and a second P-type 3C-SiC layer is grown to obtain an epitaxial structure;

[0270] The flow rate of the carrier gas used in the etching is 100 slm, the flow rate of the carbon source gas is 20 sccm, the temperature is 1520°C, the pressure is 100 mbar, and the time is 2 min;

[0271] The flow rate of the carrier gas used in the growth of the buffer layer is 100 slm, the flow rate of the silicon source gas used is 100 scmm, the flow rate of the carbon source gas used is 30 sccm, the flow rate of the N-type dopant used is 20 sccm, the growth temperature is 1520°C, the growth pressure is 100 mbar, the thickness of the obtained buffer layer is 0.5 μm, and the doping concentration of the obtained buffer layer is 1×10 17 atom / cm 3 ;

[0272] The flow rate of the carrier gas used in the growth of the first N-type 4H-SiC layer is 100 slm, the flow rate of the silicon source gas used is 600 scmm, the flow rate of the carbon source gas used is 400 sccm, the flow rate of the N-type dopant used is 10 sccm, the growth temperature is 1520°C, the growth pressure is 100 mbar, the thickness of the obtained N-type 4H-SiC layer is 30 μm, and the doping concentration of the obtained N-type 4H-SiC layer is 2×10 16 atom / cm3 ;

[0273] The flow rate of the carrier gas used in the growth of the second N-type 4H-SiC layer is 100 slm, the flow rate of the silicon source gas used is 600 scmm, the flow rate of the carbon source gas used is 400 sccm, the flow rate of the N-type dopant used is 10 sccm, the growth temperature is 1520°C, the growth pressure is 100 mbar, the thickness of the obtained N-type 4H-SiC layer is 0.5 μm, and the doping concentration of the obtained N-type 4H-SiC layer is 2×10 16 atom / cm 3 ;

[0274] The flow rate of the carrier gas used in the growth of the first P-type 3C-SiC layer is 100 slm, the flow rate of the silicon source gas used is 400 scmm, the flow rate of the carbon source gas used is 800 sccm, the flow rate of the P-type dopant used is 5 sccm, the growth temperature is 1350°C, the growth pressure is 100 mbar, the growth rate is 1 μm / h, the thickness of the obtained P-type 3C-SiC layer is 1 μm, and the doping concentration of the obtained P-type 3C-SiC layer is 2×10 16 atom / cm 3 ;

[0275] The flow rate of the carrier gas used in the growth of the second P-type 3C-SiC layer is 100 slm, the flow rate of the silicon source gas used is 800 scmm, the flow rate of the carbon source gas used is 400 sccm, the flow rate of the P-type dopant used is 80 sccm, the growth temperature is 1350°C, the growth pressure is 100 mbar, the growth rate is 2 μm / h, the thickness of the obtained P-type 3C-SiC layer is 0.5 μm, and the doping concentration of the obtained P-type 3C-SiC layer is 1×10 17 atom / cm 3 ;

[0276] In this embodiment, the carrier gas used is hydrogen, the silicon source gas used is SiHCl3; the carbon source gas used is C2H4, the N-type dopant used is NH3, and the P-type dopant used is TMAl.

[0277] Example 4

[0278] This embodiment provides a bonded composite substrate, the bonded composite substrate comprising: a polycrystalline SiC layer 1, a first 4H-SiC layer 2, a 3C-SiC layer 3, and a second 4H-SiC layer 4 bonded in sequence;

[0279] The thickness of the polycrystalline SiC layer 1 is 370 μm; the thickness of the first 4H-SiC layer 2 is 0.7 μm; the thickness of the 3C-SiC layer 3 is 0.3 μm; and the thickness of the second 4H-SiC layer 4 is 0.7 μm.

[0280] The preparation process is as follows:

[0281] Performing a first bonding between the 4H-SiC layer implanted with the first ions and the polycrystalline SiC layer, followed by a first stripping and a first polishing to obtain a first bonding body;

[0282] Performing a second bonding between the first bonding body and the 3C-SiC layer implanted with the second ions, and then performing a second peeling and a second polishing to obtain a second bonding body;

[0283] The second bonding body and the 4H-SiC layer after the third ion implantation are subjected to a third bonding, followed by a third stripping and polishing to obtain a bonded composite substrate;

[0284] The 4H-SiC layer used in the first ion implantation includes an N doping concentration of 1×10 19 atom / cm 3 , 4H-SiC single crystal layer with a 4° angle in the <11-20> direction; the first ion implantation dosage is 12×10 15 atom / cm 2 The injection energy is 90 keV, the injection angle is 20°, and the injection depth is 1 μm; the first bonding method is Ar ion activation, and the bonding strength is 1.8 J / m 2 The temperature of the first peeling is 150°C and the time is 45 min. The surface roughness Ra of the first bonded body obtained after the first polishing is 0.11 nm.

[0285] The 3C-SiC layer used in the second ion implantation is a 3C-SiC single crystal layer with a 4° inclination in the <11-20> direction; the implantation dose of the second ion implantation is 20×10 15 atom / cm 2 The injection energy is 95 keV, the injection angle is 5°, and the injection depth is 0.5 μm; the second bonding method is Ar ion activation, and the bonding strength is 1.85 J / m 2 The temperature of the second peeling is 300°C and the time is 30 min. The surface roughness Ra of the second bonded body obtained after the second polishing is 0.08 nm.

[0286] The 4H-SiC layer used in the third ion implantation is a 4H-SiC single crystal layer with a 4° orientation in the <11-20> direction; the implantation dose of the third ion implantation is 25×10 15 atom / cm 2 The injection energy is 80 keV, the injection angle is 20°, and the injection depth is 0.5 μm; the third bonding method is Ar ion activation, and the bonding strength is 1.95 J / m 2The temperature of the third peeling is 300°C and the time is 30 min. The surface roughness Ra of the bonded composite substrate obtained after the third polishing is 0.12 nm.

[0287] This embodiment provides an epitaxial structure, which includes, from bottom to top:

[0288] The bonded composite substrate 100 , the buffer layer 200 , the first N-type 4H—SiC layer 300 , the second N-type 4H—SiC layer 400 , the first P-type 3C—SiC layer 500 , and the second P-type 3C—SiC layer 600 .

[0289] The preparation process is as follows:

[0290] The bonded composite substrate is sequentially etched, a buffer layer is grown, a first 4H-SiC layer is grown, a second 4H-SiC layer is grown, a first P-type 3C-SiC layer is grown, and a second P-type 3C-SiC layer is grown to obtain an epitaxial structure;

[0291] The flow rate of the carrier gas used in the etching is 500 slm, the flow rate of the carbon source gas is 10 sccm, the temperature is 1580°C, the pressure is 50 mbar, and the time is 1 min;

[0292] The flow rate of the carrier gas used in the growth of the buffer layer is 500 slm, the flow rate of the silicon source gas used is 50 scmm, the flow rate of the carbon source gas used is 80 sccm, the flow rate of the N-type dopant used is 30 sccm, the growth temperature is 1580°C, the growth pressure is 50 mbar, the thickness of the obtained buffer layer is 2 μm, and the doping concentration of the obtained buffer layer is 2×10 18 atom / cm 3 ;

[0293] The flow rate of the carrier gas used in the growth of the first N-type 4H-SiC layer is 500 slm, the flow rate of the silicon source gas used is 300 scmm, the flow rate of the carbon source gas used is 600 sccm, the flow rate of the N-type dopant used is 5 sccm, the growth temperature is 1580°C, the growth pressure is 50 mbar, the thickness of the obtained N-type 4H-SiC layer is 5 μm, and the doping concentration of the obtained N-type 4H-SiC layer is 0.5×10 16 atom / cm 3 ;

[0294] The flow rate of the carrier gas used in the growth of the second N-type 4H-SiC layer is 500 slm, the flow rate of the silicon source gas used is 300 scmm, the flow rate of the carbon source gas used is 600 sccm, the flow rate of the N-type dopant used is 5 sccm, the growth temperature is 1580°C, the growth pressure is 50 mbar, the thickness of the obtained N-type 4H-SiC layer is 2 μm, and the doping concentration of the obtained N-type 4H-SiC layer is 4×1016 atom / cm 3 ;

[0295] The flow rate of the carrier gas used in the growth of the first P-type 3C-SiC layer is 500 slm, the flow rate of the silicon source gas used is 800 scmm, the flow rate of the carbon source gas used is 400 sccm, the flow rate of the P-type dopant used is 10 sccm, the growth temperature is 1400°C, the growth pressure is 50 mbar, the growth rate is 2 μm / h, the thickness of the obtained P-type 3C-SiC layer is 0.5 μm, and the doping concentration of the obtained P-type 3C-SiC layer is 1×10 16 atom / cm 3 ;

[0296] The flow rate of the carrier gas used in the growth of the second P-type 3C-SiC layer is 500 slm, the flow rate of the silicon source gas used is 400 scmm, the flow rate of the carbon source gas used is 800 sccm, the flow rate of the P-type dopant used is 50 sccm, the growth temperature is 1400°C, the growth pressure is 50 mbar, the growth rate is 1 μm / h, the thickness of the obtained P-type 3C-SiC layer is 2 μm, and the doping concentration of the obtained P-type 3C-SiC layer is 5×10 17 atom / cm 3 ;

[0297] In this embodiment, the carrier gas used is hydrogen, the silicon source gas used is SiH2C12, the carbon source gas used is C3H8, the N-type dopant used is N2, and the P-type dopant used is TMAl.

[0298] Comparative Example 1

[0299] The only difference from Example 1 is that the 3C-SiC layer is replaced by a 4H-SiC layer of equal thickness.

[0300] Comparative Example 2

[0301] The only difference from Example 1 is that the 3C-SiC layer is replaced by a SiC layer of equal thickness.

[0302] Comparative Example 3

[0303] The only difference from Example 1 is that the 3C-SiC layer is replaced by a 6H-SiC layer of equal thickness.

[0304] Comparative Example 4

[0305] The only difference from Example 1 is that the first 4H-SiC layer is replaced by a 6H-SiC layer of equal thickness.

[0306] Comparative Example 5

[0307] The only difference from Example 1 is that the second 4H-SiC layer is replaced by a 6H-SiC layer of equal thickness.

[0308] Comparative Example 6

[0309] The only difference from Example 1 is that the first 4H-SiC layer is replaced by a 3C-SiC layer of equal thickness.

[0310] Comparative Example 7

[0311] The only difference from Example 1 is that the second 4H-SiC layer is replaced by a 3C-SiC layer of equal thickness.

[0312] Comparative Example 8

[0313] The only difference from Embodiment 1 is that the first N-type 4H-SiC layer is not provided in the epitaxial structure.

[0314] Comparative Example 9

[0315] The only difference from Embodiment 1 is that no second N-type 4H-SiC layer is provided in the epitaxial structure.

[0316] Comparative Example 10

[0317] The only difference from Embodiment 1 is that the first P-type 3C-SiC layer is not provided in the epitaxial structure.

[0318] Comparative Example 11

[0319] The only difference from Embodiment 1 is that no second P-type 3C-SiC layer is provided in the epitaxial structure.

[0320] The epitaxial structures obtained in the embodiment and the comparative example were tested for breakdown voltage according to GB / T 29332-2012 to characterize the withstand voltage performance. The results are shown in Table 1 below.

[0321] Table 1

[0322] Breakdown voltage / V Example 1 1657 Example 2 1734 Example 3 1638 Example 4 1724 Comparative Example 1 1522 Comparative Example 2 1492 Comparative Example 3 1309 Comparative Example 4 1459 Comparative Example 5 1521 Comparative Example 6 1562 Comparative Example 7 1469 Comparative Example 8 1589 Comparative Example 9 1592 Comparative Example 10 1585 Comparative Example 11 1579

[0323] As can be seen from Table 1, the solution provided by the present invention adopts a specifically designed bonding structure to form a quantum well at the bonding interface of the 3C-SiC layer and the 4H-SiC layer, so that the stacking fault is extended to the bonding interface, thereby avoiding the stacking fault from extending to the single crystal layer or even the epitaxial layer, thereby improving the voltage resistance performance. At the same time, the resulting bonded composite substrate has a lower surface free energy, which can prevent the thin single crystal layer from being etched through.

[0324] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0325] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0326] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A bonded composite substrate, characterized in that: The bonded composite substrate comprises: a polycrystalline SiC layer, a first 4H-SiC layer, a 3C-SiC layer and a second 4H-SiC layer bonded in sequence.

2. The bonded composite substrate according to claim 1, wherein: The thickness of the polycrystalline SiC layer is 330-370 μm; Preferably, the thickness of the first 4H-SiC layer is 0.3-0.7 μm; Preferably, the thickness of the 3C-SiC layer is 0.3-0.7 μm; Preferably, the second 4H-SiC layer has a thickness of 0.3-0.7 μm.

3. A method for preparing a bonded composite substrate as claimed in claim 1 or 2, characterized in that: The preparation method comprises: Performing a first bonding between the 4H-SiC layer implanted with the first ions and the polycrystalline SiC layer, followed by a first stripping and a first polishing to obtain a first bonding body; Performing a second bonding between the first bonding body and the 3C-SiC layer implanted with the second ions, and then performing a second peeling and a second polishing to obtain a second bonding body; The second bonding body and the 4H-SiC layer that has been subjected to the third ion implantation are subjected to the third bonding, and then subjected to the third stripping and polishing to obtain a bonded composite substrate.

4. The preparation method according to claim 3, characterized in that: The 4H-SiC layer used in the first ion implantation includes an N doping concentration of 5×10 18 -1×10 19 atom / cm 3 , 4H-SiC single crystal layer with a 4° deviation in the <11-20> direction; Preferably, the implantation dose of the first ion implantation is ≥10×10 15 atom / cm 2 ; Preferably, the implantation energy of the first ion implantation is ≥80keV; Preferably, the implantation angle of the first ion implantation is 5°-20°; Preferably, the implantation depth of the first ion implantation is 0.5-1 μm; Preferably, the first bonding method includes Ar ion activation; Preferably, the bonding strength of the first bonding is > 1.5 J / m 2 ; Preferably, the temperature of the first peeling is 150-300°C; Preferably, the first peeling time is 30-45 minutes; Preferably, the surface roughness Ra of the first bonding body obtained after the first polishing is less than 0.2 nm.

5. The preparation method according to claim 3 or 4, characterized in that: The 3C-SiC layer used in the second ion implantation includes a 4° 3C-SiC single crystal layer in the <11-20> direction; Preferably, the implantation dose of the second ion implantation is ≥10×10 15 atom / cm 2 ; Preferably, the implantation energy of the second ion implantation is ≥80keV; Preferably, the implantation angle of the second ion implantation is 5°-20°; Preferably, the implantation depth of the second ion implantation is 0.5-1 μm; Preferably, the second bonding method includes Ar ion activation; Preferably, the bonding strength of the second bonding is > 1.5 J / m 2 ; Preferably, the temperature of the second stripping is 150-300°C; Preferably, the second peeling time is 30-45 minutes; Preferably, the surface roughness Ra of the second bonding body obtained after the second polishing is less than 0.2 nm; Preferably, the 4H-SiC layer used in the third ion implantation comprises a 4H-SiC single crystal layer with a 4° deflection in the <11-20> direction; Preferably, the implantation dose of the third ion implantation is ≥10×10 15 atom / cm 2 ; Preferably, the implantation energy of the third ion implantation is ≥80keV; Preferably, the implantation angle of the third ion implantation is 5°-20°; Preferably, the implantation depth of the third ion implantation is 0.5-1 μm; Preferably, the third bonding method includes Ar ion activation; Preferably, the bonding strength of the third bonding is > 1.5 J / m 2 ; Preferably, the temperature of the third peeling is 150-300°C; Preferably, the third peeling time is 30-45 minutes; Preferably, the surface roughness Ra of the bonded composite substrate obtained after the third polishing is less than 0.2 nm.

6. An epitaxial structure, characterized in that: The epitaxial structure comprises the bonded composite substrate as claimed in claim 1 or 2.

7. The epitaxial structure according to claim 6, characterized in that: The epitaxial structure includes, from bottom to top: The composite substrate, the buffer layer, the first N-type 4H-SiC layer, the second N-type 4H-SiC layer, the first P-type 3C-SiC layer and the second P-type 3C-SiC layer are bonded.

8. A method for preparing an epitaxial structure according to claim 6 or 7, characterized in that: The preparation method comprises: The bonded composite substrate is sequentially etched, a buffer layer is grown, a first N-type 4H-SiC layer is grown, a second N-type 4H-SiC layer is grown, a first P-type 3C-SiC layer is grown, and a second P-type 3C-SiC layer is grown to obtain an epitaxial structure.

9. The preparation method according to claim 8, characterized in that: The flow rate of the carrier gas used in the etching is 100-500slm; Preferably, the flow rate of the carbon source gas used in the etching is 10-20 sccm; Preferably, the etching temperature is 1520-1580°C; Preferably, the etching pressure is 50-100 mbar; Preferably, the etching time is 1-2 min; Preferably, the flow rate of the carrier gas used in the growth of the buffer layer is 100-500slm; Preferably, the flow rate of the silicon source gas used in the growth of the buffer layer is 50-100 scmm; Preferably, the flow rate of the carbon source gas used in the growth of the buffer layer is 30-80 sccm; Preferably, the flow rate of the N-type dopant used in the growth of the buffer layer is 20-30 sccm; Preferably, the growth temperature of the buffer layer is 1520-1580°C; Preferably, the growth pressure of the buffer layer is 50-100 mbar; Preferably, the thickness of the buffer layer obtained by growing the buffer layer is 0.5-2 μm; Preferably, the doping concentration of the buffer layer obtained by growing the buffer layer is 1×10 17 -2×10 18 atom / cm 3 ; Preferably, the flow rate of the carrier gas used in the growth of the first N-type 4H-SiC layer is 100-500slm; Preferably, the flow rate of the silicon source gas used in the growth of the first N-type 4H-SiC layer is 300-600 scmm; Preferably, the flow rate of the carbon source gas used in the growth of the first N-type 4H-SiC layer is 400-600 sccm; Preferably, the flow rate of the N-type dopant used in the growth of the first N-type 4H-SiC layer is 5-10 sccm; Preferably, the growth temperature of the first N-type 4H-SiC layer is 1520-1580° C.; Preferably, the growth pressure of the first N-type 4H-SiC layer is 50-100 mbar; Preferably, the thickness of the N-type 4H-SiC layer obtained by growing the first N-type 4H-SiC layer is 5-30 μm; Preferably, the doping concentration of the N-type 4H-SiC layer obtained by growing the first N-type 4H-SiC layer is 0.5×10 16 -2×10 16 atom / cm 3 ; Preferably, the flow rate of the carrier gas used in the growth of the second N-type 4H-SiC layer is 100-500slm; Preferably, the flow rate of the silicon source gas used in the growth of the second N-type 4H-SiC layer is 300-600 scmm; Preferably, the flow rate of the carbon source gas used in the growth of the second N-type 4H-SiC layer is 400-600 sccm; Preferably, the flow rate of the N-type dopant used in the growth of the second N-type 4H-SiC layer is 5-10 sccm; Preferably, the growth temperature of the second N-type 4H-SiC layer is 1520-1580° C.; Preferably, the growth pressure of the second N-type 4H-SiC layer is 50-100 mbar; Preferably, the thickness of the N-type 4H-SiC layer obtained by growing the second N-type 4H-SiC layer is 0.5-2 μm; Preferably, the doping concentration of the N-type 4H-SiC layer obtained by growing the second N-type 4H-SiC layer is 2×10 16 -4×10 16 atom / cm 3 ; Preferably, the flow rate of the carrier gas used in the growth of the first P-type 3C-SiC layer is 100-500slm; Preferably, the flow rate of the silicon source gas used in the growth of the first P-type 3C-SiC layer is 400-800 scmm; Preferably, the flow rate of the carbon source gas used in the growth of the first P-type 3C-SiC layer is 400-800 sccm; Preferably, the flow rate of the P-type dopant used in the growth of the first P-type 3C-SiC layer is 5-10 sccm; Preferably, the growth temperature of the first P-type 3C-SiC layer is 1350-1400° C.; Preferably, the growth pressure of the first P-type 3C-SiC layer is 50-100 mbar; Preferably, the growth rate of the first P-type 3C-SiC layer is 1-2 μm / h; Preferably, the thickness of the P-type 3C-SiC layer obtained by growing the first P-type 3C-SiC layer is 0.5-1 μm; Preferably, the doping concentration of the P-type 3C-SiC layer obtained by growing the first P-type 3C-SiC layer is 1×10 16 -2×10 16 atom / cm 3 ; Preferably, the flow rate of the carrier gas used in the growth of the second P-type 3C-SiC layer is 100-500slm; Preferably, the flow rate of the silicon source gas used in the growth of the second P-type 3C-SiC layer is 400-800 scmm; Preferably, the flow rate of the carbon source gas used in the growth of the second P-type 3C-SiC layer is 400-800 sccm; Preferably, the flow rate of the P-type dopant used in the growth of the second P-type 3C-SiC layer is 50-80 sccm; Preferably, the growth temperature of the second P-type 3C-SiC layer is 1350-1400° C.; Preferably, the growth pressure of the second P-type 3C-SiC layer is 50-100 mbar; Preferably, the growth rate of the second P-type 3C-SiC layer is 1-2 μm / h; Preferably, the thickness of the P-type 3C-SiC layer obtained by growing the second P-type 3C-SiC layer is 0.5-2 μm; Preferably, the doping concentration of the P-type 3C-SiC layer obtained by growing the second P-type 3C-SiC layer is 1×10 17 -5×10 17 atom / cm 3 .

10. A power device, characterized in that: The power device comprises the bonded composite substrate as claimed in claim 1 or 2.

Citation Information

Cited By

  • SiC epitaxial wafer and preparation method thereof

    CN120184006A